NEUROCYSTICERCOSIS, A RARE BUT NOT UNCOMMON CAUSE OF EPILEPSY - Farahana Mohd Saharuddin; Nur Ilya Syafiqah Mohd Yusri; Wahinuddin Sulaiman; Chong Li Ann; Azzahra Nurul Azman (Asian Journal of Medicine & Health Sciences, 2020)
Neurocysticercosis is considered to be endemic in many underdeveloped countries. In Malaysia, neurocysticercosis cases are rarely reported. We report a local born Malay Muslim man who had been diagnosed with epilepsy for the past 7 years, presented with a breakthrough seizure and altered behavior. Computed tomography (CT) scan of the brain showed multiple hyperdense lesions suggestive calcified rings with possible dead parasite within it. Toxoplasma IgG was positive while IgM was negative. Neurocysticercosis is treated with cysticidal drugs such as albendazole or Praziquantel. Albendazole is the drug of choice as its anti-parasitic effect is superior compared to Praziquantel.